Strategi Pengembangan Obyek Desa Wisata Kandri Kecamatan Gunung Pati Kota Semarang - Muhammad Tofan; Ari Subowo; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Tourism contributes in the creation of work,the business world society wage,local revenue,foreign exchange to country. Kampung wisata Kandri divides into four RW each have the potential and distinctive cloistral. Were along RW I was education tourism as education nature. In RW II as a plantation arena is equipped with a variety of fruit and in this later developed as arena outbound. RW III as the cultural area, and in the RW IV is focus on typical food stalls. This research use SWOT analysis. The research of this strategy based on Litmus analysis there are any six strategic issues : Establishing facilities and infrastructure, an increase in the quantity and quality of human resources, development of quality tourism object, increasing promotion strategies, increasing coordination between local communities with tourism department and related parties, increasing.